2008
DOI: 10.1007/s10948-008-0372-6
|View full text |Cite
|
Sign up to set email alerts
|

Electron–Phonon Interaction and Phonon Renormalization in the Lamellar Cobaltate Na x CoO2

Abstract: We study theoretically the electron-phonon interaction in Na x CoO 2 . For the A 1g and E 1g phonon modes found in Raman experiments, we calculate the matrix elements of the electron-phonon interaction. Analyzing the feedback effect of the conduction electrons on the phonon frequency ω, we investigate the doping dependence of these two phonon modes. Due to the momentum dependence of the electron-phonon interaction, we find the strongest renormalization of the E 1g mode around the Brillouin zone boundary which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…[58] It is also supported by other investigations, which have found that the A1g mode shows a strong coupling to conduction electrons. [68,69] While the effects of excitonic contributions likely have to be included to obtain quantitative agreement (e.g., for the speed of the gap dynamics), [66] the qualitative picture of the onset of a phase transition due to ultrafast optical excitation can be described by coherent phonons. In such a model, carrier multiplication also has an contribution to the dynamics of the coherent phonon amplitude, as we show in the following.…”
Section: Carrier Dynamics Via Equation Of Motion Technique a Optical ...mentioning
confidence: 99%
“…[58] It is also supported by other investigations, which have found that the A1g mode shows a strong coupling to conduction electrons. [68,69] While the effects of excitonic contributions likely have to be included to obtain quantitative agreement (e.g., for the speed of the gap dynamics), [66] the qualitative picture of the onset of a phase transition due to ultrafast optical excitation can be described by coherent phonons. In such a model, carrier multiplication also has an contribution to the dynamics of the coherent phonon amplitude, as we show in the following.…”
Section: Carrier Dynamics Via Equation Of Motion Technique a Optical ...mentioning
confidence: 99%